DBGC 3 – A promising genotype of desi chickpea for north east plain of India - Choudhary, A K; Kumar, Santosh; Shubha, Kumari (Indian Farming, 2024)
Chickpea (Cicer arietinum L.) is an important crop in semi-arid regions, constituting an important component of low input agriculture in India. Since independence, the area and productivity of this crop has substantially increased. However, there has been substantial shift in area from north to south zones. This shift has been ascribed largely to the competition of chickpea with high-yielding cereal crops and emergence of other root diseases aside from Fusarium wilt. As a result, both area and productivity of chickpea have gone down in the north east plains. This requires sustainable breeding efforts to develop high-yielding chickpea genotypes with inbuilt resistance to major root diseases for cultivation in the north east plains. The development of ‘DBGC 3’ is a step forward in this direction.